Diri yang Pra-Deskriptif: (Studi Paralelisme Struktur Fundamental Manusia Dalam Filsafat Heidegger dan Mullā Şadrā) - Refan Aditya (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2021)
This study discusses the thoughts of two great philosophers namely Martin Heidegger and Mulla Ṣadrā in a study of Philosophy of Man in the topic of ‘Fundamental Structure of Man’. The problem discussed here is parallelism of the philosophers' ideas on the Fundamental Structure of Man. This study tries to figure out the nature of humans according to the philosophy of Martin Heidegger and Mullā Ṣadrā, and synthesizes them with the method of parallelism. The author feels that this research is important, not only to enrich the inter-philosophical dialogue, but also because these two philosophers share the same ontological principle in their philosophical foundation namely, Being. This view is called ontological reduction. Both were convinced that no philosophical problem could be solved unless the question of Being was adequately answered. The method used in this study is the particular comparative method, namely parallelism. From this research the author found that, Parallelism of the Fundamental Structure of Man according to Heidegger and Mulla Ṣadrā shows a criticism of the views that have taken root in the discourse of modern Western philosophy which was pioneered by Rene Descartes. Heidegger clearly shows his disagreement with the view of self in Cartesian philosophy and breaks it down with the idea of human Dasein as an existent who understands himself in a pre-structured understanding, existentially and precedes any reflection or any cognitive activity about I (self). Likewise Mullā Ṣadrā, who lived in the same century as Rene Descartes, indirectly criticized such philosophical traditions of rationalism by developing the idea of his ‘ilm hudhūrī, that this knowledge of I or self (self-knowledge) is immanent in itself (self-evident) and precede any form of conception or reflection about self and be the basis for every form of empirical knowledge.